"Modified Adductor Sling Technique"- a surgical therapy for patellar instability in children and adolescents. Issue 3 (23rd March 2016) - Alm, Lena; Frosch, Karl-Heinz; Preiss, Achim; Heitmann, Maximilian; Akoto, Ralph
Aims and Objectives: Due to open femoral physis, the therapy of patellar instability in children and adolescents is challenging. We developed a surgical technique, modified form of the "Adductor-Sling-Technique" by Sillanpää which offers a surgical treatment to avoid damage to the femoral physis. The purpose of this study is to determine whether there is a benefit in the clinical outcome for patients operated by the "modified Adductor Sling Technique" in comparison to patients with other surgical procedures. Materials and Methods: Twenty "modified Adductor Sling" reconstructions in 19 patients (age 11-24) were included in the study until now, 15 patients with open physis and 4 patients with closed physis with special indications. Since 2010 "modified Adductor Sling" reconstruction was performed by looping the gracilis tendon around the adductor magnus tendon and attaching it at the medial facette of the patella. Clinical outcome was retrospectively evaluated at a mean follow-up period of 1.3 years (range 0.5-3.6). The evaluation also included Lysholm Score, Kujala Score and DGU score. Statistical analysis was performed using IBM®SPSS®Statistics Version 21. A P value less than 0.5 was considered significant. Results: The average age at the time of operation was 14.9 years (range 11.2-24.3). Recurrent dislocation occurred in 4 out of 20 cases (20%). It was noticeable that out of those 4 patients 2 patients had a lateral release in addition to the "modified Adductor Sling Technique" due to lateral hyperpression. No other patients had a lateral release in our patient population. Also, out of those 4 patients 3 patients had an additional maltracking of the patella, caused by a high TTTG, severe trochlea dysplasia or additional axial deformity. The overall Kujala Score was 87 (range 46-100) points, in patients without re-dislocation it was 94 (range 46-100) points. The overall Lysholm Score was 85 (range 39-100) points, in the group without re-dislocation 90 (range 39-100) points. The mean TTTG was 16, 59 (range 11, 7-21, 4) mm, in the group without re-dislocation it was 16, 24 (range 11, 7-21, 4) mm. There was no significant difference between the patients with or without re-dislocation(p=0, 312). Conclusion: The "modified Adductor Sling Technique" offers relevant clinical improvements in knee function and pain. An advantage is the avoidance of damaging the femoral physis. Our Hypothesis of less recurrent dislocation rates could not be confirmed. The re-dislocation rate was even higher than in MPFL reconstruction using femoral fixation in adults. Patients with patellar instabilities without maltracking (no severe trochlea dysplasia, no axial deformity, moderately elevated TTTG) and open physis benefit from the "modified Adductor Sling Technique". This technique is not recommended in patients with patellar instability and additional maltracking.